Design and Construction of Air Quality Monitoring System using Node MCU IoT Based - Wulandari, Vivi; Yohandri, - (Department of Physics – Universitas Negeri Padang UNP, 2024)
Air as a natural resource affects human life and other natural resources. Air consists of about 78% Nitrogen, 20% Oxygen, 1.07% consists of Neon (Ne), Helium (He), Methane (CH4) and Hydrogen (H2), 0.9% Argon and the remaining 0.03% Carbon Dioxide (CO2). This research is a type of engineering research. Data collection was carried out by direct measurement. For direct data collection, it was carried out by monitoring levels of CO2, CO, temperature, and humidity, for data collection from each parameter, 5 variations were given for measurement. Based on the objectives of the research, the results of the design specifications of the tool are obtained, namely the percentage level of accuracy of the average measurement produced by air quality monitoring which is 97.78%, the average percentage of relative error obtained is 2.24%. Therefore, it can be concluded that the specifications for the performance of the tool are that the components that make up the tool can work well